Kelengkapan dan Keakuratan Sertifikat Medis Penyebab Kematian di Rumah Sakit Umum Pusat Fatmawati - Yuni Marugun; Gama Bagus Kuntoadi (APIKES Bhumi Husada Jakarta, 2015)
Abstract Fatmawati Central General Hospital (RSUP) is a government’s hospital of type A which has the purpose of providing a full service. To achieve its objectives, the RSUP Fatmawati will always strive to improve the quality of service, including providing complete and accurate medical information. To achieve the full service, RSUP Fatmawati has work units that have their duties and obligations. One of them is Medical Record Installation and Health Information (IRMIK) which one of its duty is to make monthly report of mortality. In order to create a good and complete mortality report, IRMIK requires a complete and accurate data source in the form of Medical Cause of Death Certificate (SMPK) from Forensic Installation (IFPJ). From the initial research found the existence of some SMPK columns that are not filled completely by the doctor in charge. The incompleteness of filling the SMPK in Fatmawati Central General Hospital is the reason behind this followed research. The research was conducted in May 2013 located in RSUP Fatmawati, South Jakarta, Indonesia. The research was conducted using qualitative descriptive approach by focusing on completeness and accuracy of SMPK form filling. From the result of the research, it was found that most of the incompleteness of the contents occurred in the Population Identity Number column as much as 100%, then in the cause of death collum also found not fully filled, so it can be concluded the average completeness of filling of Medical Cause of Death Certificate in RSUP Fatmawati in May 2013 is 84%. Keyword : medical record, medical cause of death certificate, incompleteness, inaccuracies